Trajetórias tecnológicas da indústria de telefonia móvel: um exame prospectivo de tecnologias emergentes - Neris Junior, Celso; Fucidji, José Ricardo [UNESP]; Gomes, Rogério (Instituto de Economia da Universidade Estadual de Campinas, 2014)
The mobile phone industry has undergone important changes in recent years. Its market structure and boundaries have been affected by the introduction of innovations of new entrants to the industry, who have come from other sectors of the Information and Communication Technologies (ICT) complex. This paper aims to describe this process, by analyzing three features of this industry: (i) its technological trajectory; (ii) the development and introduction of new technologies; and (iii) the positioning of new players in the international production of knowledge. In doing so, the literature on innovations in the telecommunications industry will be drawn upon to identify, describe and evaluate relevant players and promising technologies. Having designed the sample of firms and technologies, some aspects of the new technologies selected are presented, followed by a bibliometric analysis of three of them - internet protocol (IPv6), wireless connection (802.11n) and near field communications (NFC). Besides claiming our proposed methodology as a valuable tool for technological foresight, the findings point to two main conclusions. First, the opportunities created by the introduction of new trajectories unleashed a process of digital convergence within the mobile phone industry, and allowed the entry of new firms into it. This process is changing the market structure of the industry, changing strategies and performance of its incumbents and leaders and blurring the boundaries of markets within the ICT complex. Secondly, it seems that these developments are making it possible for American corporations to regain their lost technological hegemony over the industry and Asia appears to be emerging as a definitive player in the production of relevant scientific and technological knowledge in these fields.

A indústria de telequipamentos, em especial a de telefonia móvel, passou por transformações importantes nos últimos anos. A estrutura e as fronteiras do mercado foram modificadas pela introdução de inovações de produtos por empresas que há pouco atuavam em outros setores do complexo das Tecnologias de Informação e Comunicação (TICs). Este estudo procura descrever este processo, analisando três aspectos da indústria: (i) as trajetórias tecnológicas, (ii) o surgimento de novas tecnologias e (iii) a inserção de novos atores na produção internacional de conhecimento. Para fazê-lo, o trabalho revisa a literatura sobre inovações nesta indústria para, a seguir, identificar, descrever e avaliar os atores e as tecnologias promissoras. Definida uma amostra de novas tecnologias, o trabalho sistematiza suas características e procede à análise bibliométrica de três delas - protocolo de internet (IPv6), rede sem fio (802.11n) e transmissão de dados a curta distância (NFC). Além de estabelecer a metodologia adotada como um interessante instrumento de prospecção tecnológica, os resultados encontrados permitem duas conclusões principais. A primeira aponta que as oportunidades abertas pelo surgimento de novas trajetórias desencadearam um processo que está permitindo a entrada de novos atores, especialmente de empresas vindas de outras atividades no campo das TICs e que tornam imprecisas as fronteiras dos mercados e alteram o desempenho e a estratégia de empresas já consolidadas e líderes do setor. A segunda sugere que os EUA buscam recuperar a hegemonia perdida e que a Ásia está definitivamente inserida na produção de conhecimento científico-tecnológico relevante nesta indústria.
Technological trajectories of the mobile telephone industry: a prospective analysis of emergent technologies
Keywords: Telefonia móvel; Trajetórias tecnológicas; Tecnologias emergentes; Novos atores; Divisão internacional do trabalho; Mobile phone industry; Technological trajectories; Emerging technologies; New actors; International division of labor